Zonificación de amenazas geológicas por movimientos en masa que permitan el ordenamiento territorial en la urbanización Ciudad de Victoria de Loja. - Villalta Castillo, Azucena Ondina (2011)
The city of Loja, located to the South of the Ecuadorian Andes, presents an irregular topography which has been modified by the quick urbanization process where the populational establishments have been overturned predominantly to the western side of the city and whose floor use doesn't correspond to the process of physical-space growth, with citadels, urbanizations and lotizaciones that occupy qualified surfaces as non urbanizables, so much for geologic limitations, geotécnicas or topographical, like for its natural interest. The study area to be located in an area exposed to various types of mass movements due to various factors in geography and geology, determine areas susceptible. Geological structures such as fractures, faults and microfallas present in the sector and the presence of soft sedimentary rocks of low resistance and very weathered significantly affect the generation of large-scale landslides with volume shifted between 100 and 1000m3. In addition the ground floor consists of soft sand, clay and low resistance, have been the main cause for the generation of cracks in roads and housing sector. The contributions of water are considered as the factor in the occurrence of movements, as these alter the mechanical and physical properties of soil and rock so that analyzed the range of rainfall for the area of study, which found that rainfall between 800mm 1200 mm / year, from January to April being the rainiest period, which significantly influences the generation of mass movements. Based on the features found in the urbanization "Ciudad Victoria" considered as conditioning factors, intervention estimated anthropogenic and meteorological factors as triggers, are evidence of mass movements that threaten the lives of the inhabitants of the area. Factors analyzed that allowed establishing degrees of susceptibility and threatens to stop to avoid loss of life, economic and environmental.